Development of an intelligent wireless network for microgrid - Tay, Kelvin Kian Ming. (2012)
Microgrid is an integrated energy system consisting of a low-voltage distribution network with distributed energy resources (DER) such as fuel cells, solar photovoltaics and wind turbines. Traditionally, monitoring and control in Microgrid depend vastly on wireline communications. This project will focus on developing an intelligent wireless network using wireless communications such as RF, ZigBee or WiMAX to communicate with DER for real-time monitoring and control purposes. With the build-in sensors in DER, data are transmitted using wireless communication to a main server and displayed through a GUI. The collected data will be used to study the performance of DER.